Molecular cloning and characterization of MPL, the human homolog of the v-mpl oncogene: identification of a member of the hematopoietic growth factor receptor superfamily. - Vigon, I (1992)
We have cloned the human homolog of the v-mpl oncogene transduced in the myeloproliferative leukemia retrovirus, which presents striking homologies with members of the hematopoietin receptor superfamily. We obtained two types of clones, MPLP and MPLK, which had the same 5' extremity but differed at their 3' ends. The resulting deduced polypeptides are composed of a common extracellular domain with a putative signal sequence and a common transmembrane domain, but they differ in their cytoplasmic domain after a stretch of 9 common amino acids. The extracellular domain of MPL contains the consensus sequences described for the members of the hematopoietin receptor superfamily. In addition, as for murine interleukin 3 and human and murine granulocyte-macrophage colony-stimulating factor type beta receptors, this domain can be divided into two subunits. An additional motif specific for MPL could be displayed by hydrophobic cluster analysis in the first subdomain. When RNAs from various hematopoietic cell lines were analyzed by Northern blot, MPL was detected only in the human erythroleukemia (HEL) cell line as a major 3.7-kilobase (kb) mRNA (MPLP) and a minor 2.8-kb mRNA (MPLK). However, study of MPL expression by PCR analysis indicated that MPL is expressed at a low level in a large number of cells of hematopoietic origin and that the two types of mRNAs (P and K) were always found to be coexpressed.